Modernization Of Post-Al-Nahdah Arabic Literary Criticism - Qur’aniyul Farid, Muhammad Jillul; Julkarnain, Rangga Iskandar (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This paper aims to examine the modernization of post-al-Nahdah Arabic literary criticism. Especially in the aspect of the historicity of its development from time to time until after the al-Nahdah era. This research uses a historical approach and descriptive-qualitative methods. . The type of research is library research, through data collection by tracing reading sources such as relevant journals and books and analyzing these sources rigidly. The results of the study found that literature always experiences changes in terms of its knowledge, because literature is a cultural product that often interacts with the conditions of the surrounding world, especially the Western world. The changes that occur affect other studies that are closely related to literature, such as the study of Arabic literary criticism. Arabic literary criticism developed along with the emergence of the modernization movement in the al-Nahdah era. The writers and figures of Arabic literary criticism tried to develop the characteristics of Arabic literary criticism by adopting Western concepts so that the study of Arabic literary criticism could develop in line with the development of science. Therefore, several new methodologies and approaches emerged as a variety of richness of literary studies, especially Arabic literary criticism studies.